Social Network Forensics, Cyber Security, and Machine Learning - Krishna, P. Venkata; Gurumoorthy, Sasikumar; Obaidat, Mohammad S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the issues and challenges in Online Social Networks (OSNs). It highlights various aspects of OSNs consisting of novel social network strategies and the development of services using different computing models. Moreover, the book investigates how OSNs are impacted by cutting-edge innovations.
,b.cn';fgjl['mkj'/.bv 1.Online Social Networks -- 2.Trust in Online Social Networks -- 3.Big Data and Online Social Networks -- 4.IoT and Online Social Networks -- 5.Privacy in Online Social Networks -- 6.Social Network Analysis -- 7.Mobile Cloud Computing Vs. Online Social Networks -- 8.Reputation and trust prediction in OSN -- 9.Social and cultural differences in perception and participation -- 10.Online Social Networks on users, culture, and society -- 11.Online Social Networks in health, entertainment and education services .
Keywords: Computational intelligence; Big data; Neural networks (Computer science) .; Signal processing; Application software; Computational Intelligence; Big Data; Mathematical Models of Cognitive Processes and Neural Networks; Signal, Speech and Image Processing; Computer and Information Systems Applications